Analysis of Articulation of Local Government Financial Statements - Muliyadi Hamid (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The Financial and Development Supervisory Agency (BPKP) stated that the non-obtainment of WTP's opinion was due to several factors. The factor is the presentation of financial statements that do not follow government accounting standards (SAP). The study aims to see the suitability of the Palopo City LKPD, which has the opinion of WTP (2021-2020) with government regulation number 71 of 2010 concerning government accounting standards (SAP). To answer these problems, researchers use descriptive qualitative research methods using documentation techniques to collect data. In this study, there were 27 OPDs and one LKPD, which were the object of analysis with accrual-based articulation analysis. The analysis was conducted by comparing the facts in the front sheet of OPD and LKPD financial statements with criteria based on accounting equations and government accounting standards (SAP). The results of this study showed that for the financial statements of 27 OPDs, 4 OPDs achieved 100% articulation, and 23 OPDs achieved 96.67% articulation, with an average cumulative articulation value of all OPDs of 97.16%. In contrast, for the analysis of LKPD articulation, the results of 100% articulation achievements were found to be two types of articulation with 23 events in the OPD financial statements.